Era Daniel um revolucionário macabeu? Os santos e a revolta macabaica a partir da análise exegética e histórica de Daniel 8,1-14 - Alves, Carolina Campos (2021)
The second century BC was a very troubled period in Judea during the Seleucid rule under Antiochus IV Epiphanes. In the midst of so many events, a rebel group stands up against the current government. The present research has as its base text the passage of Daniel, the apocalyptic narrative about Daniel’s vision of a ram and a goat fighting with each other until the ram be annihilated by its opponent. For a better comprehension of our research we have divided it into three parts. In our first part, we presented an overview of Daniel’s book, followed by the presentation of out text and an exegetical study of our passage, Dn 8,1-14. In the second part, we presented from the elements raised in the exegesis carried out the historical context referred to by the author’s narrative. In our last part of our research, we resumed some concepts, words dealt with in the first part and deepened their study with the objective of analyzing the similarities between the narrative and a rebel group, the Maccabees.